Perpaduan Serasi, Penggagas Inovasi - Astini, Fatin Nuha (Jurnal Administrasi Publik, 2014)
Abstract: Harmonious Coherence, Initiators of Innovation. This study start from two assumption. First, innovation need an initiator as a pionerr, innovator, secondly, in the governance there should be a combination of stakeholders. Innovative governance needed to answer an increasingly diverse public issues varied, to create it, isn’t easy, it requires a combination of initiator and stakeholders. This study used a qualitative approach and data analysis spradley models. The result, two assumptions are manifested in Innovative Governance through Malnutrition Poverty Movement (GENTASIBU), an innovative program initiated Nganjuk regent wife , came from the response of the high rates of malnutrition, then, innovator raises an idea that as a solution, its shaped GENTASIBU. Not only raises, but also the innovator consistent fight for her idea, until formally approved by regents decision letter, 188/ 140/ K/ 411 013/ 2009. The success of this innovation can not be separated from the harmonious cooperation among stakeholders, and in some other places, the two arguments are not fulfilled. Keyword: Innovative Governance, Coherence of Stakeholder’s, Initiators of Innovation Abstrak: Perpaduan Serasi, Penggagas Inovasi. Penelitian ini berawal dari dua asumsi. Pertama, bahwa inovasi membutuhkan seorang inisiator sebagai pelopor, pengagas inovasi, kedua, di dalam governance harus ada perpaduan stakeholders. Innovative governance diperlukan guna menjawab beragam permasalahan publik yang kian variatif, untuk menciptakanya bukanlah hal mudah, maka diperlukan seorang inisiator dan perpaduan stakeholders. Penelitian ini menggunakan pendekatan kualitatif dan analisis data model spradley. Hasilnya, dua asumsi tersebut telah diwujudkan dalam gerakan pengentasan gizi buruk (GENTASIBU), sebuah program inovatif yang digagas istri bupati Kabupaten Nganjuk, berawal dari daya tanggapnya terhadap tingginya angka gizi buruk, selanjutnya penggagas memunculkan suatu gagasan sebagai penyelesai, yaitu berbentuk suatu gerakan pengentasan gizi buruk. Tidak hanya memunculkan namun penggagas juga konsisten mengembangkan gagasan, memperjuangkan hingga disahkan secara resmi melalui Surat Keputusan Bupati No. 188/ 140/ K/ 411.013/ 2009. Keberhasilan inovasi ini juga tidak terlepas dari hasil kerjasama yang serasi antar stakeholders, dan di beberapa tempat lain, dua argumen tersebut belum tentu dapat terpenuhi. Kata Kunci: Innovative Governance, Perpaduan Peran Stakeholders, Penggagas Inovasi